Gaya Hidup Konsumtif Generasi Z dan Kaitannya dengan Inflasi dalam Perspektif Ekonomi Syariah - Annisa Annisa; Norbaiti Norbaiti; Walinasifa Walinasifa; Norkhadizah Makkiah; Muhammad Iqbal Sanjaya (Journal of Islamic Economics and Finance, 2025)
This study aims to provide an overview of the consumption patterns of Generation Z and how they relate to inflation from an Islamic economics perspective. A library research strategy is used in this investigation. Information was gathered from a number of sources, such as books, journals, and other problem-related scientific resources. The results indicate that Gen Z's consumption habits could lead to demand-pull inflation, or an increase in inflation. Prices rise when the supply cannot keep up with the substantial increase in demand for products and services brought on by consumer behavior. When Gen Z consumes technology, fashion, entertainment, and food items all of which are frequently popular and seasonal this issue becomes more noticeable. Consumption is controlled in Islamic economics to avoid becoming wasteful (tabzir) or excessive (israf). Needs (maslahah), not only wants or carnal emotions, must be the basis for consumption. The primary remedy, according to Islamic economics, is to emphasize beneficial consumption, Islamic-based money management, and bolstering social and spiritual values in order to curb consumption and prevent detrimental effects on people or the economy.